Arabic Language Instruction Through YouTube-Based Vlogs To Enhance The Arabic Speaking Proficiency Of Students At Darul Falah Amtsilati - Rohman, Mujibur; Al Anshory, Abdul Muntaqim (Jurnal Bahasa Arab, 2025)
This study aims to describe the effectiveness of using YouTube-based vlogs to enhance students' speaking skills (mahārah kalām) at Darul Falah Amtsilati Islamic Boarding School. Employing a descriptive qualitative approach, the research involved students from the Darussalam dormitory as its subjects. Data were collected through observation, interviews, documentation, and performance assessments of the vlogs. The findings reveal that using vlog media positively impacted the development of students’ speaking skills, particularly in fluency, sentence structure accuracy, self-confidence, and the ability to express ideas creatively and communicatively. Although restrictions on the use of mobile devices within the boarding school posed a challenge, assigning vlog-making projects during school holidays proved to be an innovative solution that remained within institutional regulations. Furthermore, the students responded positively to this method, increasing learning motivation and developing 21st-century skills. This study recommends integrating digital media, such as vlogs, into Arabic language instruction as an educational innovation aligned with contemporary needs.